COMMUNICATIVE POTENTIAL AS MAIN COMPONENT OF THE CULTURE OF COMMUNICATION OF THE FUTURE TEACHERS (Pedagogy of Higher and Secondary Education, 2004)
The principal constituents of communicative potential are revealed in the article. The necessity of taking it into consideration while forming communicative culture of future teachers.